O ENFRENTAMENTO DA CORRUPÇÃO NO ESTADO DO MARANHÃO: mecanismos de atuação do Ministério Público de Contas. - PINHEIRO, Analissa Barros (2019)
This paper aims to contribute to the discussion about the performance of the Public Prosecutor's Office of the State of Maranhão, regarding the confrontation of corruption. In this way, it brings together elements that allow us to understand how the aforementioned institutional body has acted in confronting corruption, through the use of its institutional mechanisms, seeking to encourage transparency, morality and ethics in Public Administration. In this sense it brings considerations about the problematization developed by the research, as well as its presuppositions, justification, besides its methodology. It also promotes an approach on corruption in the Brazilian public administration, bringing historical and conceptual considerations. It also analyzes the organs of external control and the confrontation of corruption in Brazil with conceptual and normative approaches. It also analyzes the Brazilian Public Prosecutor's Office in the historical and legislative perspective, as well as discusses the institution, as well as relating its institutional mission to the fight against corruption in Brazil. Finally, it makes a study about the Public Prosecutor's Office of the State of Maranhão, regarding their attributions and how this institution promotes the confrontation of corruption in the State of Maranhão. Finally, to identify and analyze the mechanisms of control of corruption used by the Public Prosecutor's Office of Maranhão, as well as a study compared with the external control models of Brazil, Chile and Uruguay, in order to identify similar organs to the Public Prosecutor's Office of bills.